Minimalisasi Kegagalan Sirkulasi Pengembalian Feed pada Mesin Pellet di PT Charoen Pokphand Indonesia Feedmill - Linardi, Stefanie Mariana; Octavia, Tanti (Jurnal Titra, 2015)
One of the most common problem happened at PT. Charoen PokÂphand Indonesia is the failure in feed collection systems on pellet machine. This failure should be minimized since it creates huge loss in terms of downtime in the working process of the pellet machine. The failure is analysed using 5 Whyâs and Failure Mode Effect Analysis (FMEA) to find the source of the failure. From the analysis, the proposed improvements are to change the parts of feed collection systems and to create a guidance in maintaining and monitoring feed collection systems. The failure in feed collection systems did not happen anymore after the proposal is implemented with the saving costs of manufacturing as Rp472.500.000,00 per month.